Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.2147/ijn.s42723
|View full text |Cite
|
Sign up to set email alerts
|

Formulation, characterization, and expression of a recombinant MOMP Chlamydia trachomatis DNA vaccine encapsulated in chitosan nanoparticles

Abstract: Chlamydia trachomatis is a bacterial sexually transmitted infection affecting millions of people worldwide. Previous vaccination attempts have employed the recombinant major outer membrane protein (MOMP) of C. trachomatis nonetheless, with limited success, perhaps, due to stability, degradation, and delivery issues. In this study we cloned C. trachomatis recombinant MOMP DNA (DMOMP) and encapsulated it in chitosan nanoparticles (DMCNP) using the complex coacervation technique. Physiochemical characterizations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…The morphology of nanoparticles was assessed using SEM (Zeiss EVO 50 VPSEM) and TEM (Zeiss EM10 TEM) as recently published 1618 . For SEM, nanoparticles were mounted on metal pegs using conductive double-sided tape and sputter coated with a gold layer prior to examination.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The morphology of nanoparticles was assessed using SEM (Zeiss EVO 50 VPSEM) and TEM (Zeiss EM10 TEM) as recently published 1618 . For SEM, nanoparticles were mounted on metal pegs using conductive double-sided tape and sputter coated with a gold layer prior to examination.…”
Section: Methodsmentioning
confidence: 99%
“…The mean sizes and zeta potentials of nanoparticles were measured using a zetasizer Nano-ZS instrument (Malvern Instruments, UK) 1618 . Each nanoparticle sample was measured in triplicates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies using recombinant MOMP encapsulated in PLGA demonstrated enhanced induction of Th1 cytokines and cellular and antibody immune responses (189,190). Cambridge et al demonstrated that MOMP was expressed in the tissues and organs of mice that were intramuscularly injected with chitosan nanoparticles containing recombinant MOMP DNA (191).…”
Section: Biodegradable Polymersmentioning
confidence: 99%
“…Mice vaccinated with the nanoparticle-detained toxin showed superior protective immunity against toxin-mediated adverse effects; effective virulence neutralization of toxins and 100% survival rate were achieved. Moreover, natural polymers such as chitosan and pullulan have also been utilized for delivery of antigen against bacteria such as C. trachomatis and Streptococcus pneumoniae [172,173]. Interestingly, chitosan was also reported to have adjuvant properties through the promotion of cytokine production.…”
Section: Antimicrobial Nanovaccinementioning
confidence: 99%